2019
DOI: 10.1192/bjp.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

The CORE service improvement programme for mental health crisis resolution teams: results from a cluster-randomised trial

Abstract: BackgroundCrisis resolution teams (CRTs) offer brief, intensive home treatment for people experiencing mental health crisis. CRT implementation is highly variable; positive trial outcomes have not been reproduced in scaled-up CRT care. AimsTo evaluate a 1-year programme to improve CRTs' model fidelity in a non-masked, cluster-randomised trial (part of the Crisis team Optimisation and RElapse prevention (CORE) research programme, trial registration number: ISRCTN47185233). MethodFifteen CRTs in England received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 27 publications
(48 reference statements)
2
51
1
1
Order By: Relevance
“…Priorities for the development and validation of the CORE CRT Fidelity Scale are discussed elsewhere (Lloyd‐Evans et al, ): they include further exploration of its reliability; establishing its criterion validity, and its relationship to key CRT outcomes; and testing its international applicability in non‐UK settings. The feasibility of utilizing the scale in research has been demonstrated by its use in a cluster‐randomized trial of a CRT service improvement intervention (Lloyd‐Evans et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Priorities for the development and validation of the CORE CRT Fidelity Scale are discussed elsewhere (Lloyd‐Evans et al, ): they include further exploration of its reliability; establishing its criterion validity, and its relationship to key CRT outcomes; and testing its international applicability in non‐UK settings. The feasibility of utilizing the scale in research has been demonstrated by its use in a cluster‐randomized trial of a CRT service improvement intervention (Lloyd‐Evans et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Work in this area has been undertaken as part of the CORE study. The results of a cluster‐randomized trial evaluating a CRT service improvement programme (Lloyd‐Evans et al, ; Lloyd‐Evans et al, ) demonstrate that such interventions are feasible, acceptable and can increase model fidelity and reduce inpatient admissions. Better understanding of the impact of, and barriers and facilitators to, implementation of such improvement programmes is needed, and a qualitative analysis of these issues from the CORE study will be available shortly.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of staff participants was 43 years (SD 10 years) at baseline and follow-up; the majority identified as female (66% at baseline and 63% at follow-up) and white (68% at baseline and 65% at follow-up). (For further information about recruitment rates and service user and staff participants' characteristics, see the paper 84 referred to in Appendix 6.) No serious adverse events (SAEs) were identified during participant recruitment and data collection, and no study-related harms were reported by participating CRTs during the trial intervention.…”
Section: Resultsmentioning
confidence: 99%
“…No significant association was found between the change in fidelity scores and changes in hospital admission rates, inpatient bed-days or staff well-being. For a breakdown of CRTs' fidelity scores and relationships with outcomes, see the paper 84 referred to in Appendix 6. The qualitative evaluation established three broad domains capturing stakeholder views and experiences of the SIP (for a more detailed description, see Appendix 7):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation